Referral in a routine Italian optometric examination: towards an evidence-based model. - Cheloni, Riccardo; Swystun, Alexander G; Frisani, Mauro; Davey, Christopher J (Scandinavian Journal of Optometry and Visual Science, 2021)
Italian optometrists refract patients and prescribe optical appliances. The routine optometric examination that is currently conducted in Italy, however, does not include a comprehensive ocular health assessment. Like many other countries, in Italy ophthalmologists are solely responsible for the diagnosis and treatment of ocular pathologies, yet, the care an optometrist provides must be done with the aim of promoting the general and ocular health of patients seen in practice. Such scope has to be pursued using a close collaboration with ophthalmologists, ultimately facilitating the earliest medical diagnosis and minimisation of visual impairment. Referral represents the basis of optometrist-ophthalmologist collaboration, yet, no guidance is available to Italian optometrists indicating when referral is warranted. The purpose of this study was to identify the circumstances deserving a referral in a routine Italian optometric examination in adults, ultimately constituting preliminary evidence-based indications of a referral model oriented to enhance the ocular and general health of patients. A literature review was conducted on Pubmed and the Cochrane Library, mainly targeting high quality secondary literature such as systematic reviews, meta-analysis and clinical guidelines. Several reasons for referral were identified. Further, while a wide range of anomalies of the visual system are likely to be discovered by the Italian optometric examination, up to 20% of patients could suffer an underlying condition undetected by the current assessment. This results in the need to refer seemingly healthy patients if they have not attended routine ophthalmological examinations within optimal time frames. In Italy, and countries with similar settings, the referral is an essential instrument that optometrists must largely use to ensure early diagnosis of ocular conditions by ophthalmologists and minimisation of avoidable visual impairment.